Induction of Symbiosis in Tridacna crocea (C. Bivalvia, F. Tridacnidae) Using Zooxanthellae from T. gigas and from T. crocea: Effects on Clam Survival and Growth - Mingoa-Licuanan, S. Suzanne (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Survival and growth of post-metamorphic Tridacna crocea juveniles were improved by inducing symbiosis with fresh or cloned zooxanthellae (Tg10) derived from T. gigas. Although clam growth was best with Tc4, survival was also poorest. Symbiosis with specific zooxanthellae was established at the pediveliger stage, with reinfection a few days after. It is suggested that while survival and growth may be easily monitored and may be used as indicators of good performance of a functional holobiont, other phenotypic traits such as resistance to disease, bleaching, etc. may also be considered in evaluating the effectivity of the selected zooxanthellae.
Keywords: symbiosis; Tridacna crocea; zooxanthellae; Tridacna gigas; survival; growth